Lelkigondozás és pasztorálpszichológia – átfedések és különbségek - NÉMETH, Dávid (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2023)
Pastoral Care and Pastoral Psychology – Overlaps and Differences Pastoral psychology suffers from a chronic identity crisis. It wants to be a theological science while at the same time meeting the criteria for the scientific practice of psychology. Is there a way to maintain this dual identity? Only if we assume that beliefs play an enormous role in understanding and modifying human experience and behaviour. Beliefs are assumptions about the meaning of reality. They have both psychological and theological aspects. Pastoral psychology examines how psychological explanations can be linked to the insights of the Christian faith in understanding and modifying the processes of interpreting reality. For pastoral care, it develops approaches and offers methods for helping people from the perspective of the Christian faith to evaluate themselves realistically, to shape their social relationships positively, and to relate constructively to events that affect their lives.